2015
DOI: 10.1016/j.jairtraman.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The evolving low-cost business model: Network implications of fare bundling and connecting flights in Europe

Abstract: The evolving low-cost business model: network implications of fare bundling and connecting flights in Europe 1. Introduction Low-cost travel is becoming the dominant way of flying within Europe (Dobruszkes, 2013). However, there are signs of a slowdown in the organic growth of low-cost carriers (LCC) due to decreasing average frequencies and increasing average route distances, which is forcing LCC to adopt other business strategies for growth (de Wit and Zuidberg, 2012), including the possibility of establishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 38 publications
4
63
0
4
Order By: Relevance
“…Hence, the expression LCC, in fact, covers multiple business models that differ to a greater or lesser extent in their elements (Mason and Morrison, 2008). However, they all coexist under the low-cost label (Fageda et al, 2015).…”
Section: Business Model Convergencementioning
confidence: 99%
“…Hence, the expression LCC, in fact, covers multiple business models that differ to a greater or lesser extent in their elements (Mason and Morrison, 2008). However, they all coexist under the low-cost label (Fageda et al, 2015).…”
Section: Business Model Convergencementioning
confidence: 99%
“…O setor aéreo passou por uma desregulamentação mundialmente, como verificado por Fageda et al (2015), o que proporcionou para as companhias flexibilização na escolha de tarifas Todos as informações e direitos sobre o presente artigo são de total e única responsabilidade do(s) autor(es). mais tardiamente, quando os sucessivos esforços para conter a inflação no final da década de 1980 fracassaram e as políticas de controle de preços reduziram as receitas das companhias aéreas.…”
Section: Revisão Literatura a Caracterização Do Setor Aéreounclassified
“…Moreover, in recent years there has been a drift away from the use of secondary airports and indeed in a study of 20 European LCCs, Klophaus et al (2012) only found three airlines that used predominantly secondary airports. One of the major trends has been LCCs moving into primary airports for a number of reasons including a more convenient location, which will be more attractive to business markets and provide an opportunity for flight connections, at the same time as limits to growth for secondary airports due to market maturity (de Wit, 2012;Fageda et al, 2015). At primary airports the LCCs may also be able to offer a pricing premium, compete head-on with network carriers or feed/code-share their services.…”
Section: Development Of the Lcc Sectormentioning
confidence: 99%